Initial development of seedlings of Bauhinia variegata L. and Ceiba speciosa (A. St. Hil.) Ravenna under substrates based on poultry litter - Krefta, Sandra Mara; Brun, Eleandro José; Facchi, Suelen Pietrobon; dos Santos, Luana Maria; Klein, Danieli Regina; Krefta, Sandiane Carla; Germano, Aline Delfino; Frigeri, João Vitor (Scientia Agraria Paranaensis, 2017)
The aim of this study was to evaluate the initial development of seedlings of Bauhinia variegata L. and Ceiba speciosa (A.St.Hil.) Ravenna under different rations of poultry litter on their substrate. The five substrates formulated from poultry litter were: T1: control substrate (SC); T2: 33.3% (S) soil, 33.3% sand (A) and 33.3% % of poultry litter (CA); T3: 25% S, 25% A, 50% CA; T4: 16.6% S, 16.6% A, 66.6% CA; T5: 100% CA. The variables analyzed at the third month of the seedlings were: colon diameter (DC), height of the seedlings (H) and number of leaves (NF), relationship between height and colon diameter (H/DC) (MSA), roots dry mass (MSR), total dry mass (MST), relation between shoot dry mass and root dry mass (MSA/MSR) and Dickson Quality Index (IQD). The analysis of the results was performed statistically in terms of variance (ANOVA) and test of comparison of means, for which the Tukey test was used, with a confidence level of 95% using the software Assistat 7.6 beta. From the results, it can be concluded that all substrates studied were suitable for the development of B. variegata and C. speciosa seedlings. However, the use of poultry litter becomes interesting in the production of seedlings. The incorporation of this organic material, besides adding nutrients to the substrate, optimizes the correct destination of the same and reduces the cost of the substrate.